Internalisasi Nilai-Nilai Islam Melalui Program Jumat Barokah Dalam Membentuk Karakter Religius Peserta Didik SMK Negeri 3 Tuban - Muhammad Faliq Mubarrok Ilmi; Iis Aisaroh (Advances In Education Journal, 2025)
Student misconduct, including bullying and brawls, reflects a decline in religious character formation. This study describes the internalization of Islamic values through the "Jumat Barokah" program at SMK Negeri 3 Tuban. Employing a descriptive qualitative method, data were collected via interviews, observations, and documentation involving the principal, teachers, and students. Findings reveal that the program consistently implements Friday routines, including Dhuha prayers, dhikr, tausiyah, and voluntary charity. This systematic habituation has successfully improved students' spiritual awareness and moral conduct. In conclusion, "Jumat Barokah" effectively builds religious character, though its long-term impact requires extended observation to ensure full trans-internalization. Future research should cover longer periods to validate the sustainability of these behavioral changes.